Abdominal Contents from Two Large Early Cretaceous Compsognathids (Dinosauria: Theropoda) Demonstrate Feeding on Confuciusornithids and Dromaeosaurids - Xing, Lida; Bell, Phil R.; Persons, W. Scott, IV; Ji, Shuan; Miyashita, Tetsuto; Burns, Michael E.; Ji, Qiang; Currie, Philip J. (PLOS ONE, 2012)
Two skeletons of the large compsognathid Sinocalliopteryx gigas include intact abdominal contents. Both specimens come from the Jianshangou Beds of the lower Yixian Formation (Neocomian), Liaoning, China. The holotype of S. gigas preserves a partial dromaeosaurid leg in the abdominal cavity, here attributed to Sinornithosaurus. A second, newly-discovered specimen preserves the remains of at least two individuals of the primitive avialan, Confuciusornis sanctus, in addition to acid-etched bones from a possible ornithischian. Although it cannot be stated whether such prey items were scavenged or actively hunted, the presence of two Confuciusornis in a grossly similar state of digestion suggests they were consumed in rapid succession. Given the lack of clear arboreal adaptations in Sinocalliopteryx, we suggest it may have been an adept stealth hunter.